GESETZ BEI APOSTEL PAULUS UND FRANZISKUS VON ASSISI AUS DER PERSPEKTIVE VON GIORGIO AGAMBEN UND ALAIN BADIOU. - Pawlak, Kamil (2025)
At a time when, in Western culture, states and international communities attempt to juridically circumscribe every detail of not only public, but also family and personal life, one notices the delegation of personal responsibility to legal regulations and institutions. Such a solution often seems to make life easier in a complex and fast-paced reality but leads to the abandonment of participation in public life and the shaping of the world as a personal subject. As a result, man, his society, economics and politics become less human. The phenomenon of the replacement of the personal dimension of man by law has been dealt with in recent decades, particularly by the Italian philosopher Giorgio Agamben braving the French philosopher and mathematician Alain Badiou, both of whom refer to the writings of Saint Paul the Apostle in their refl ections on law. Paul underwent an inner transformation from a man ruthlessly subject to the law to a man totally devoted to the person of Jesus Christ. Agamben sees the most eff ective application of Paul’s doctrine of freedom from the law in how Saint Francis and his fi rst brothers realized submission to the person of Jesus and obedience to his Gospel. Francis’s equating of Rule and form of life off ers hope for overcoming today’s dehumanizing dictatorship of law.
Keywords: Apostles; Families; Francis, of Assisi, Saint, 1182-1226; LEGAL liability; Responsibility; Western Civilization